Correlation of CD10 immunoexpression and eosinophil count in stromal tissue as predictors of prognosis of squamous cell carcinoma of the oral cavity - Patuti, Deece; Yusuf, Harmas Yazid; Hernowo, Bethy Suryawathy (Padjadjaran Journal of Dentistry, 2010)
Introduction: CD10 can also facilitate the ability of tumour metastasis by its ability to invade blood vessel walls.Correlation of CD10 immunoexpression and eosinophil count in stromal tissue as predictors of prognosis of squamous cell carcinoma of the oral cavity. Methods: This study was preceded by collecting data on squamous cell carcinoma of the oral cavity in the medical record and paraffin blocks in the Anatomy Pathology section of 15 samples with enlarged regional lymph nodes and 15 samples without enlargement of regional lymph nodes. Then two preparations were made, the first preparation was stained with Hematoxylin Eosin (HE) to establish the diagnosis and determine the histopathological gradation, then count the number of eosinophils, and the other development was smeared with CD10. Outward immunohistochemistry uses the Labelled streptavidin biotin immunoperoxidase complex (LSAB) method using the Starr Trek Universal HRP Detection system. (Biocare Medical, USA). The primary antibody used was CD10 (Novocastra Laboratories Ltd, Newcastle upon Tyne, UK) with a dilution of 1:25 - 1: 50. Results: There was no statistically significant correlation between CD10 and enlargement of the lymph node regionally tested statistically using the Spearman rank test rs = -0.236, meaning that the increase in CD10 immunoexpression is inversely proportional to the enlargement of regional lymph node, but the correlation is not statistically significant The results of the analysis using the Spearman rank test found significance of p = 0.043 (significant) with a correlation strength of 37.2% Conclusion: There was no correlation between CD10 and enlargement of the lymph node regionally and correlation strength eosinophil distribution in squamous cell carcinoma of the oral cavity without regional lymph node enlargement.